Analysis of Marine Current Turbine Placement Location in Suramadu Bridge - Indonesia - Mujahid, Ahmad Syafiul; Erwandi, Erwandi (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
Marine current turbine is a system of marine current power plant to produce renewable electrical energy derived from marine currents. After marine current turbine successfully tested in Larantuka Strait in 2010, then in 2015 marine curent turbine team from BPPH-BPPT has conducted a study for placement of marine current turbine test that located in Suramadu Bridge, Madura Strait, East Java, Indonesia. This study uses survey data technique by direct measurement; Type of survey that is conducted using sampling technique by sampling method: purposive sampling or judgemental sampling. the subject of sampling data is marine current velocity data and ocean depth data which is chosen by researcher in the waters around the pile 56 to pile 57 under Suramadu Bridge. Measurements were conducted using instruments measurement: portable sounder, flow meter, and GPS. The measurement showed average depth: 11.4 meters and average marine current velocity: 1.3 m/s. By using the Betz Law Equation then the largest electric power can be obtained: 4.507 kW that located at 4.5 meters from pile 56 location. The Computational Fluid Dynamics (CFD) simulation is conducted to obtain the position of marine current turbine placement in order that turbine blades can rotate at optimum marine current speed. The optimum placement result of marine current turbine is located at 6.3 meters from piles 56 to the center of turbine, and the furthest distance from pile 56 to the turbine blade is 8.1 meters.